Varied facets of history : essays in honour of Aniruddha Ray - Ray, Aniruddha; Alam, Ishrat; Hussain, Syed Ejaz (Primus Books, 2011)
Festschrift for Aniruddha Ray, former professor, Dept. of Islamic History and Culture, University of Calcutta; contributed articles.